APLIKASI PRESENSI PERKULIAHAN DENGAN FINGERPRINT BERBASIS WEB DAN SMS GATEWAY (Studi Kasus Universitas Kuningan) - Krisdiawan, Rio Andriyat; Irawan, Dede (TI S1 FKOM UNIKU, 2018)
The process of attendance at the Kuningan university environment greatly influences the lecture process for students, payroll for lecturers, and the process of quality services for the brass university lectures. The process of presence in the Kuningan university is still done manually, namely by writing and attending the Student and Lecturer Attendance List (DHMD). The process still has many shortcomings, such as there are still students who leave attendance in the form of signatures on DHMD, there is still a need to do a prescription when reporting data, and easily damage / lose DHMD when managing data. In addition, students sometimes cannot know directly the information on the attendance calculation of lectures that have been conducted. Based on the description above, the researcher will build a lecture presence application using fingerprint as a tool used in the presence input process, and create an effective and efficient presence management application to assist attendance management, as well as service sms gateway as notification of attendance calculation information to students and lecturers will be built with the PHP programming language with MySQL databases. As well as the concept of client server networks where all attendance data centers will be stored on the computer server that will provide the service sms gateway. The implementation will be carried out in accordance with the courses, lecturers, classes, rooms, and lectures at the University of Kuningan, specifically at the Faculty of Computer Science, Kuningan University. And testing is carried out on presence data inputted with a fingerprint scanner through applications and databases that have been built.Keywords: SMS Gateway, Fingerprint, Presence, Lecture, PHP and MySQL